2022
DOI: 10.1186/s12884-022-05114-y
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome and follow-up of offspring of donor oocytes recipient from PCOS patients

Abstract: Background The use of donated oocytes (DO) for in vitro fertilization(IVF) treatment in patients with infertility is generally recognized, and females with polycystic ovarian syndrome (PCOS) can participate in oocyte donation programs as donor patients. However, the pregnancy outcomes and offspring follow-up in patients with PCOS as the recipients are unclear. This study was to compare the pregnancy outcomes and follow-up of offspring in PCOS and non-PCOS receptor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The women were given short-time IVF protocol in the first ART treatment cycle unless accompanied with severe male-factor infertility. Oocytes were inseminated with prepared spermatozoa in 2 to 4 h after oocytes retrieval and the cumulus cells were removed mechanically after 4–5 h co-incubation for polar body observation to decide whether to perform rescue ICSI (Re-ICSI) [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…The women were given short-time IVF protocol in the first ART treatment cycle unless accompanied with severe male-factor infertility. Oocytes were inseminated with prepared spermatozoa in 2 to 4 h after oocytes retrieval and the cumulus cells were removed mechanically after 4–5 h co-incubation for polar body observation to decide whether to perform rescue ICSI (Re-ICSI) [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the four phenotypes of PCOS studied, no statistically significant differences were found in the incidence of neonatal birth weight, neonatal icterus, NICU admission, or neonatal death [ 45 ]. While a good amount of studies found additional risks, several studies found no difference in Apgar, birth weight, and incidence of hypoglycemia, which was also seen in comparing fertilization methods [ 37 , 39 , 43 , 44 , 46 ].…”
Section: Reviewmentioning
confidence: 99%
“…This trend continued during pregnancy when GDM was diagnosed, with most studies observing that pregnant women with PCOS had a significantly higher BMI [ 13 , 18 , 23 , 33 , 43 ]. Another interesting finding is that the implantation of an oocyte from a woman with PCOS into a woman without PCOS does not alter the baseline prevalence of GDM [ 46 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation